Taming Distraction: The Second Screen Assemblage, Television and the Classroom - Stauff, Markus (2016)
This article argues that television’s resilience in the current media landscape can best be understood by analyzing its role in a broader quest to organize attention across different media. For quite a while, the mobile phone was considered to be a disturbance both for watching television and for classroom teaching. In recent years, however, strategies have been developed to turn the second screen’s distractive potential into a source for intensified, personalized and social attention. This has consequences for television’s position in a multimedia assemblage: television’s alleged specificities (e.g. liveness) become mouldable features, which are selectively applied to guide the attention of users across different devices and platforms. Television does not end, but some of its traditional features do only persist because of its strategic complementarity with other media; others are re-adapted by new technologies thereby spreading televisual modes of attention across multiple screens. The article delineates the historical development of simultaneous media use as a ‘problematization’—from alternating (and competitive) media use to multitasking and finally complementary use of different media. Additionally, it shows how similar strategies of managing attention are applied in the ‘digital classroom’. While deliberately avoiding to pin down, what television is, the analysis of the problem of attention allows for tracing how old and new media features are constantly reshuffled. This article combines three arguments: (1) the second screen is conceived of as both a danger to attention and a tool to manage attention. (2) To organize attention, the second screen assemblage modulates the specific qualities of television and all the other devices involved. (3) While being a fragile and often inconsistent assemblage, the second screen spreads its dynamics—and especially the problem of attention—far beyond television, e.g. into the realm of teaching.